Characterisation of bitumen and asphalt mixture with recycled waste plastic (RWP) modified binder - Zakaria, Nur Mustakiza (2020)
Good bitumen properties are desirable nowadays to achieve longer service life. In order to enhance the quality of bitumen in term of its properties, many researchers began to focus on bitumen modifications particularly in modifying bitumen with polymer mainly from recycled waste plastic. Incorporating bitumen with polymer significantly improves and reduces asphalt pavement distresses. However, there are still some drawbacks which significantly limit its development namely inappropriate polymer and bitumen blend may result in poor storage stability that would affect the performance of asphalt mixture. Besides that, excessive hardening by adding more polymer in bitumen may increase the energy required during production which will increase the cost of the construction. Also, the modification procedure may need high shear and mixing temperature for some period that would change the rheological properties of Polymer Modified Bitumen (PMB) due to ageing. Moreover, the increasing amount of plastic waste material at the landfill is another vital concern. So, the main aim of this study is to re-use the recycled waste plastics as a modifier in bitumen to enhance the performance of asphalt mixture. Therefore, finding the optimal shear rate, modification temperature and the mixing time are essential to ensure the optimum blend of Recycled Waste Plastic (RWP) modified binder that is stable and better in performance could be produced. In this study, six types of recycled polymer and bitumen with penetration grade of 160/220 are used for the modification. Then, additional two binders namely control binder (penetration grade of 40/60) and SBS-modified bitumen were used to compare with the RWP-modified binders that gave significant improvement in terms of its performance.